Influence of oxygen flow on crystallization and morphology of LiNbO3 thin films - Simoes, A. Z.; Gonzalez, A. H.; Zaghete, M. A.; Stojanovic, B. D.; Cavalheiro, A. A.; Moeckli, P.; Setter, N.; Varela, José Arana [UNESP] (Taylor & Francis Ltd, 2002)
Polymeric precursor solution (Pechini method) was used to deposit LiNbO3 thin films by spin-coating on (100) silicon substrates. X-ray diffraction data of thin films showed that the increase of oxygen flow promotes a preferred orientation of (001) LiNbO3 planes parallel to the substrate surface. Surface roughness and grain size, observed by atomic force microscopy, change also with oxygen flow.
Keywords: crystallization; LiNbO3; rietveld analysis